High Confidence Software Reuse in Large Systems 10th International Conference on Software Reuse, ICSR 2008, Bejing, China, May 25-29, 2008 - Mei, Hong.; Mei, Hong. (Programming and Software Engineering ;, 2008)
This book constitutes the refereed proceedings of the 10th International Conference on Software Reuse, ICSR 2008, held in Beijing, China, in May 2008. The 40 revised full papers presented together with 5 workshop summaries and 5 tutorials were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on architecture and reuse approaches, high confidence and reuse, component selection and reuse repository, product line, domain models and analysis, service oriented environment, components and services, reuse approaches and frameworks, as well as reuse approaches and methods.